Nine year experience of the Northern Ireland Inherited Cardiac Conditions Service (NI ICC of slow vs. rapid ajmaline infusion protocols for the diagnosis of Brugada syndrome (BrS). (14th October 2021) - Msulaiman, H; Connolly, H; McOsker, J; Jardine, T; McCall, D; McKeown, P; Muir, A
Abstract: Background: BrS is diagnosed in patients with ST-segment elevation with type1 morphology ≥2mm in one or more leads among the right precordial leads V1 and/or V2 positioned in the second, third or fourth intercostal space, occurring either spontaneously or after provocative drug test with intravenous administration of sodium channel blockers (ie. ajmaline, flecainide, procainamide or pilsicainide). The specific protocol for Ajmaline provocation testing for diagnosis of BrS has been debated between ICC services worldwide. Concerns regarding safety and false positive rates are perceived to be associated with a more rapid infusion protocol. This retrospective observational cohort study describes the safety and positivity rates for patients undergoing ajmaline provocation challenge by both protocols over nine years. Method: Consecutive adults undergoing ajmaline challenge test from Mach 2011 to Feb 2020 were retrospectively collected. Data on patient demographics, indication for testing, genetic information, adverse events and positivity rates were compared by test protocol used. Slow protocol was defined as total dose of 1mg/kg ajmaline capped at 100mg given at rate of 10mg/min over 10 minutes. Rapid protocol was defined as 1mg/kg ajmaline capped at 100mg given over 5 minutes. Results: A total of 350 ajmaline challenges were included (275 (73%) slow vs. 75 (27%) rapid protocol) [Mean age 40±15 years; 53% male]. Indication for conducting the test was a) Family history of Brugada syndrome 164 (43%) b) Family history of SADS/SUD 103 (28%), c) OOHCA 22 (6%) d) abnormal ECG 39 (11%) and e) syncope 22 (6%). Among the positive test group, average time for test positivity is 5.92 minutes and average dose was 55mgs (p<0.05). There were no differences between positivity rate between the two protocols, group A vs. group B, p=0.45, ns. Comparison between all patients with positive vs. negative results regardless of the protocol, showed no statistical differences. Predominantly male in both groups (p=0.71, ns) and mean age of patients in their 40's (p=0.93, ns). There is a trend that positive patients likely to have family history of BrS p=0.08, ns). 2 patients had experience jaundice at later stage which resolved. Conclusion: In NI ICC service to date, we have performed 350 Ajmaline test over the last nine years. Our positivity rate was 21% (75/350). We did not identify any significant evidence of ventricular dysrhythmia (0) or QRS broadening (2) that resulting in early termination of the protocol. Abnormal ECG with absence of symptoms yields low. Therefore we will continue fast protocol in our service for efficiency in our unit. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Belfast Health and Social Care TrustCormac Felowship